The Transformation of Academic Culture in the AI Era: A Case Study of Higher Education Institutions - Erlis Warti; Rini Herminastiti (LPPM STKIP Kusuma Negara, 2026)
Students' study habits, academic relationships, and scientific integrity have been significantly impacted by the emergence of AI in higher education. However, in the case of mathematics education in Indonesia, previous studies have largely overlooked the impact of AI on students' academic culture and instead focused on the effectiveness of AI in learning. This study aims to examine how academic culture has changed in the AI era among fourth-semester students of STKIP Kusuma Negara enrolled in the Mathematics Education Study Program. The research was conducted using a case study methodology and qualitative descriptive techniques. Thirteen instructors and 15 students participated in in-depth interviews, while three others observed and documented the process. The results indicate that AI improves learning efficiency and access to academic information, but also creates technological dependency, a decline in critical thinking intensity, and dilemmas about academic integrity. The novelty of this research lies in its analysis of the transformation of mathematics education students' academic culture, encompassing changes in learning culture, intellectual interaction, and scientific integrity due to generative AI. The study recommends strengthening AI literacy, developing digital academic ethics, and designing critical thinking-based learning so that the use of AI in higher education continues to support students' academic quality